Pengaruh Penggunaan Media Puzzle Terhadap Kemampuan Kognitif Anak Usia Dini Usia 5-6 tahun di PAUD Sentuhan Kasih Abadi Tarutung - Sharlin Elviyana Harefa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study was to determine the effect of number puzzles on the arithmetic cognitive abilities of early childhood. The research hypothesis was: